Citizens' Opinion on Governmental Response to COVID-19 Outbreak: A Qualitative Study from Iran - Kamran Bagheri Lankarani PhD; Behnam Honarvar MD; Ahmad Kalateh Sadati PhD; Mohammad Reza Rahmanian Haghighi MA (SAGE Publishing, 2021)
Studying the people's expectations of government measures to control and manage the coronavirus disease 2019 (COVID-19) can help to prepare for future crises. This study aimed to investigate the opinion of the Iranian people on authorities' management during a crisis, such as the COVID-19 pandemic. This qualitative study was conducted on 70 Iranian citizens in Shiraz to explore their opinion about the government response to the COVID-19 outbreak in February and March 2020. Based on saturation criteria, the data was collected by 1 open-end question: "What is your attitude toward the readiness of the officials and government in this epidemic?" Thematic analysis was conducted to explore themes. At the first step of the outbreak, people had critical opinions on their authorities' management. Four themes were studied, including trust and responsiveness, policymaking during a health crisis, economic management, and epidemic management. Although the citizens' expectation is dynamic, our study showed that there are still high demands from citizens toward the authorities, even in a new crisis that was not perceived before. One of the best ways to respond to these demands is appropriate risk communication.